Premenstrual syndrome - theories and facts - something everyone should know - Świątek, Gabriela; Środoń, Maria; Sosnowska, Weronika; Tkaczyk, Rafał; Taracha, Kalina; Tomczyk, Jakub; Tomkiewicz, Maciej; Brzozowska, Aleksandra; Śwital, Magdalena; Tokarski, Michał (Journal of Education, Health and Sport, 2023)
Premenstrual syndrome (PMS- Premenstrual Syndrome) is a group of cyclic somatic or psychological symptoms occurring during the luteal phase of the cycle and disappearing with the onset of menstruation. The purpose of this work is to draw attention to this important but often underestimated problem, trace its pathomechanism and identify treatment methods. The interaction of many factors and predispositions is responsible for the occurrence of PMS/PMDD (PMDD- premenstrual dysphoric disorder). One of the most important is ovulatory cycles and cyclically repeated changes in ovarian hormone secretion- fluctuations in progesterone, estradiol and prolactin levels during the various phases of the cycle. The association of emotional disturbances, severe stress and disturbances in the neurotransmitter system of the central nervous system, as well as many other factors, mentioned in the article below, is described. Various methods are used to treat PMS/PMSS, ranging from less to more invasive, including lifestyle changes, cognitive-behavioral therapy, and pharmacotherapy and surgical treatment. Currently, SSRIs-serotonin reuptake inhibitors-are considered the main therapy, as well as hormonal treatment-the two-pill. A review of the literature shows that PMS/PMDD is a real problem that reduces quality of life and has a negative impact on family and social relationships. Increased public awareness and interest by physicians of many specialties in this problem will enable faster diagnosis and implementation of effective therapy, thereby minimizing the negative social impact.